PERAN GURU AKIDAH AKHLAK DALAM MENINGKATKAN KECERDASAN EMOSIONAL PESERTA DIDIK DI MI MUHAMMADIYAH NUNU - Sukrianto Sukrianto; Elya Elya; Naima Naima (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
This study is entitled "The Role of Moral Teachers in improving the emotional intelligence of students in MI Muhammadiyah Nunu Sub-district of Tatanga City hammer". In MI Muhammadiyah Nunu, Tatanga District, Palu City, (2) what are the supporting and inhibiting factors of the Akidah Akhlak and teacher increasing emotional intelligence of students in MI Muhammadiyah Nunu, Tatanga District, Palu City, the objectives of this study are: (1) to determine the role of the teacher Akidah Akhlak in increasing emotional intelligence of students in MI Muhammadiyah Nunu, Tatanga District, Palu City, (2) to determine the supporting and inhibiting factors of Akidah Akhlak teachers in improving the emotional intelligence of students in MI Muhammadiyah Nunu, Tatanga District, Palu City. This research is qualitative research. The subject of this determination is the teacher of moral subjects, data collection methods in this study are observation, interviews, and documentation. Data sources used in this study are primary data sources and secondary data sources. The research approach used in this study is the pedagogical approach, psychological approach, and social approach. Data processing techniques used are data processing techniques and data analysis. These results are obtained that the role of the Islamic Moral Teachers in increasing emotional intelligence of students in MI Muhammadiyah Nunu, Tatanga District, Palu City, namely: the teacher is able to understand the emotions of students, the teacher processes the emotions of students, provides guidance to students, provides motivation in improving emotional intelligence of students, teachers are able to foster student relations and the provision of punishment for students who violate the rules in school. The factors supporting and inhibiting the teacher's morality in developing students' emotional intelligence, namely: the existence of cooperation between teachers, increasing human resources, facilities and infrastructure, and extracurricular activities. While the inhibiting factors are: students do not obey the rules in school, students lack confidence, the demands of grades and limited time for meetings.